The influence of auxiliary gases in the optimized analysis of pulsed laser grooving of a C70S6 connecting rod for fracture splitting - S.Q. Kou (Results in Physics, 2017)
Controlled fracture splitting technology has great potential in processing the splitting parts such as engine connecting rod, and the pulsed laser processing of notches for fracture splitting, which is crucial for controlling the fracture splitting quality, is the key process. During pulsed laser grooving, auxiliary gases affect the processing quality of fracture splitting notch1 A notch as the fracture initiation source for the splitting process.1 greatly. The distribution of auxiliary gases fluid field of pulsed laser grooving for fracture splitting and the mechanism of acting of auxiliary gases was studied in this research. The simulation model of processing a single keyhole during pulsed laser grooving was established based on the depth adaptive body heat source, and then the distribution characteristics of auxiliary gases fluid field and the effects of nozzle inlet pressure on the fluid field were obtained by the finite element analysis. Research results showed that with the increase of inlet pressure, the overall pressure increased, the fluid velocity increased, the velocity attenuation was delayed in the keyhole, the velocity recovery region moves down along the notch depth, but the fluid velocity decreased when the pressure was too high; meanwhile, the turbulent kinetic energy increased with inlet pressure, and even vortex, which affected the deslagging effect of auxiliary gases, formed in the keyhole. Keywords: Pulsed laser, Grooving, Connecting rod, Fracture splitting, Fluid field